Plant nucleotide metabolism : biosynthesis, degradation, and alkaloid formation - Ashihara, Hiroshi; Ludwig, Iziar A.; Crozier, Alan (John Wiley & Sons, 2020)
"All organisms produce nucleobases, nucleosides and nucleotides of purines and pyrimidines. Plant Nucleotide Metabolism is the first book to focus on plants which exhibit important differences to other organisms in key areas of purine nucleotide metabolism and function. This book provides comprehensive information on purine nucleotide structures and metabolic pathways and the role of purine nucleotides in plant development and, when ingested, their potential effects on human health. It is a unique resource on a diversity of topics and as such is essential reading for students, researchers, and lecturers in plant biochemistry, physiology, chemistry, agricultural sciences, nutrition and the associated applied fields of research. Topic covered include: Structures of Nucleotide-Related Compounds Nucleotide Biosynthesis and Interconversions Salvage Pathways of Purine Nucleotide Biosynthesis Interconversion of Nucleotides Growth and Development Environmental Effects Biosynthesis of Purine Alkaloids Physiological and Ecological Aspects of Purine Alkaloid Biosynthesis Metabolism of Purine Alkaloids and Biotechnology Bioavailability and Potential Impact on Health of Caffeine, Theobromine and Trigonelline Nucleotides are a basic unit of DNA and fulfil several functions. This proposed book will describe the biochemistry of plant nucleotide metabolism including plant specific metabolites, such as caffeine, nicotine and cytokinins. In addition to the biosynthesis and degradation pathways, their function in plants and some applications for biotechnology such as genetic engineering to produce transgenic plants for agriculture and drug production. Although basic plant biochemistry books which include nucleotide metabolism have been published, only a few pages have been allotted to the description of nucleotides. There are some reviews on nucleotide and nucleotide-derived alkaloids, however, these articles describe the current topics for the specialists and lack even basic information on plant nucleotide metabolism. There are some excellent nucleotide books on animals and microorganisms, but no such book has been published on plants. Therefore, this will be the first book devoted to plant nucleotides. Plants produce some alkaloids from nucleotides, the contents of plant nucleotide metabolism is distinct from those in other organisms"--